The cruel prince - Black, Holly (Hot Key Books, 2018)
Of course I want to be like them. They're beautiful as blades forged in some divine fire. They will live forever... And Cardan is even more beautiful than the rest. I hate him more than all the others. I hate him so much that sometimes when I look at him, I can hardly breathe. One terrible morning, Jude and her sisters see their parents murdered in front of them. The terrifying assassin abducts all three girls to the world of Faerie, where Jude is installed in the royal court but mocked and tormented by the Faerie royalty for being mortal. As Jude grows older, she realises that she will need to take part in the dangerous deceptions of the fey to ever truly belong. But the stairway to power is fraught with shadows and betrayal. And looming over all is the infuriating, arrogant and charismatic Prince Cardan.